Effectiveness of Immediate Homework Correction in Primary Level - Regmi, Bhanu Bhakta (Journal of Gurubaba, 2024)
This article entitled "Effectiveness of Immediate Homework Correction in Primary Level" aims to find out effectiveness of immediate homework correction in primary level. For the study, eighteen students of grade four were selected from secondary school of Surkhet. The researcher himself was involved in the practical teaching for the purpose of carrying out the research. The test was the major tool for data collection. The two groups were evaluated on the basis of time duration; immediate and delay. The experimental group was taught as immediate and controlled group was taught as delay homework correction. Finally both group were compared to find out the effectiveness of immediate homework correction. From the study, it has been found that the average increased score of experimental group 83.4 percent was better than that of controlled group 74.3 percent. The difference between the scores is that of 9.1 percent.